(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article examines the relationship and treatment of epilepsy in the elderly in Uzbekistan with concomitant somatic diseases such as cardiovascular disease, kidney disease, gastrointestinal tract and others